Designing the human circulatory system e-module to increase student achievement - Dita, Killian Iko; Tuririday, Helena Trivona; Damopolii, Insar; Latjompoh, Masra (Univeritas Papua, 2023)
The purpose of this study was to develop an e-module that has valid and practical criteria in the subject of the human circulatory system in class VIII SMP. The development model used is the ADDIE development model. The research subjects were 12 students of class VIII. The instruments used are validation sheets, questionnaires and learning achievement tests. The results of the study showed: (1) an average of 87.14% was obtained from media experts for validity and 88.3% for material experts from material experts. Student responses obtained an average score of 80.4 which indicates that the e-module is very practical to use. The average n-gain of class VIII students is 0.945 with a high interpretation. So it can be concluded that e-module on human circulatory system material are valid, practical, and can improve student learning outcomes. Trials for the implementation phase of ADDIE need to be carried out to find out the effectiveness of the e-module.